2018
DOI: 10.18787/jr.2018.25.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Saddle Nose Deformity as a Result of an Aseptic Nasal Abscess Accompanied by Ulcerative Colitis and Pyoderma Gangrenosum

Abstract: Ulcerative colitis (UC) is a chronic inflammatory bowel disease (IBD) that causes granulomatous inflammation in the mucous membrane of the intestinal tract, especially in the colon. Additionally, UC can be accompanied by extraintestinal manifestation (EIM). EIM of UC includes cutaneous lesions such as pyoderma gangrenosum, and rarely, systemically occurring aseptic abscesses (AA) have been reported in a few cases. Nasal involvement of UC as an extraintestinal manifestation of IBD is rare, and few reports of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Representative extra-intestinal manifestations of UC include anemia, arthropathy, uveitis, hepatobiliary disease, and pyoderma gangrenosum (PG) (Magro et al 2017). Recently, aseptic nasal septal abscess has also been reported as a rare manifestation of PG in patients with UC (Yilmaz et al 2011;Chang 2018;Tomioka et al 2018;Yu et al 2020) (Table 1). Additionally, leukocytoclastic vasculitis (a form of small-vessel vasculitis) is one of the extra-intestinal manifestations of UC, and it has been reported that 41% of patients with UC complicated with leukocytoclastic vasculitis are positive for ANCA (Pantic et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Representative extra-intestinal manifestations of UC include anemia, arthropathy, uveitis, hepatobiliary disease, and pyoderma gangrenosum (PG) (Magro et al 2017). Recently, aseptic nasal septal abscess has also been reported as a rare manifestation of PG in patients with UC (Yilmaz et al 2011;Chang 2018;Tomioka et al 2018;Yu et al 2020) (Table 1). Additionally, leukocytoclastic vasculitis (a form of small-vessel vasculitis) is one of the extra-intestinal manifestations of UC, and it has been reported that 41% of patients with UC complicated with leukocytoclastic vasculitis are positive for ANCA (Pantic et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, upper respiratory tract lesions of GPA often do not show typical pathological features (e.g., necrotizing granulation), posing a challenge to the diagnosis of GPA by pathology in the localized type (Harabuchi et al 2013;Sattui and Lally 2020). Also, nasal PG in patients with UC and IgA monoclonal gammopathy has been reported (Matsumura et al 1999;Isomura et al 2005;Yilmaz et al 2011;Chang 2018;Tomioka et al 2018;Yu et al 2020). However, unlike in this case, vasculitis or elevation of PR3-ANCA was not reported in any cases (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations